4(2x-8)÷4=24.4÷4
2x-8=6.1
2x-8+8=6.1+8
2x=14.1
2x÷2=14.1÷2
x=7.05;
(2)
7 |
8 |
2 |
5 |
19 |
40 |
19 |
40 |
40 |
19 |
40 |
19 |
x=
40 |
19 |
(3)
2 |
3 |
1 |
5 |
1 |
2 |
1 |
5 |
2 |
3 |
1 |
2 |
1 |
5 |
1 |
3 |
1 |
5 |
1 |
3 |
x=
5 |
3 |
(4)5x-4.5×2=
1 |
2 |
5x-9=
1 |
2 |
5x-9+9=
1 |
2 |
5x=9.5
5x÷5=9.5÷5
x=1.9.
7 |
8 |
2 |
5 |
2 |
3 |
1 |
5 |
1 |
2 |
1 |
2 |
7 |
8 |
2 |
5 |
19 |
40 |
19 |
40 |
40 |
19 |
40 |
19 |
40 |
19 |
2 |
3 |
1 |
5 |
1 |
2 |
1 |
5 |
2 |
3 |
1 |
2 |
1 |
5 |
1 |
3 |
1 |
5 |
1 |
3 |
5 |
3 |
1 |
2 |
1 |
2 |
1 |
2 |